En ekonomisk hållbar växtodling i sörmländsk mellanbygd - Kronstam, Malin; Fimmerstad, Mats (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
We have been looking at three different types of agriculture in Södermanland, in the middle east of Sweden. We call the different types for Intensive, Extensive and Mix. The purpose is to get an economic defensible plan for how to run different farm sizes. We also have been looking at the working hours and how many hours the different types will give. We have a farm called Taxinge Gods as our pilot farm. Taxinge Gods grow 407 ha land and is located 60 km southwest from Stockholm. We calculated on a 100 ha: s farm just because its easy to translate to different farm sizes. We have used customs prizes in the calculations to make it fair between different farms. Administration and maintenance of buildings is not included. Intensive, this is a model that uses the land maximum. We have grains like peaces, wheat, oats, timothy, clover, sunflowers, potatoes and maze. This means a 2725 hours of working and 679 275 Sek profit in the 407 ha case. 1097 hours of working and 247 136 Sek profit in the 100 ha case. Extensive, this is the model where we see that the farmer doesn't work full time at the farm. In this model we use crops like wheat, grass, oats and barley. This means 200 446 Sek profit and 1792 hours in the 407 ha case. 49 342 Sek profit and 441 hours in the 100 ha case. Mix, this is a blend between the other two. This model is like the pilot farm runs today. In this model we use crops like wheat, peaces, canola, oats, grass and clover. This make 399 614 Sek profit and 1492 hours in the 407 ha case. 103 654 Sek profit and 343 hours in the 100 ha case. In all of the models are fallow field and harvest of straw included. We have been looking at special crops like Maze, Sunflowers, Potatoes, Clover and Timothy . These crops are also put in different plans were we can se working hours and what we can get out of them from a economic point of view. We have tried to se where the different directions can fit in. At the pilot farm we suggest the intensive model. This fit in where it's a lot of staff and it's a lot of people passing by the farm. This will probably help to sell the products like maze and sunflowers.